»Le vstani, vbôrni národ moj, do dánes v prah teptán« - Udovič, Boštjan (Teorija in praksa, 2023)
The article presents the starting points for forming the language of diplomacy as expert language. It focuses on the question of the development of diplomatic language in Slovenia, its characteristics as well as the challenges that emerge in its formation. The author presents the meaning of the formation of terms in diplomacy in the Slovenian language, which not only enrich and create the expert diplomatic language, but also determine the degree of linguistic authenticity and statesmanship in Slovenia. The key finding of the article is that two steps are required for the development of expert diplomatic language. First, the state (i.e., the competent ministries, the Assembly, the president of the Republic etc.) should become aware that the diplomatic language in Slovenia has been relatively overlooked and is due special attention. Second, establishment of a working group is required which would connect different state actors with the aim of forming a modern linguistic corpus of terms of expert diplomatic language that would not only enrich the expert language of diplomacy and its everyday use among its practitioners, but also position the language of diplomacy among the state-building components.
Keywords: besedotvorje; Diplomacija; diplomacy; Diplomatski jezik; jezik; language; Slovenia; terminological agreement; Terminologija; terminološki dogovor; word formation